2016
DOI: 10.3390/ijms17122123
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Vertebrate Model System to Evaluate Effects of Environmental Toxicants on Cardiac Development and Function

Abstract: Environmental pollution is a serious problem of the modern world that possesses a major threat to public health. Exposure to environmental pollutants during embryonic development is particularly risky. Although many pollutants have been verified as potential toxicants, there are new chemicals in the environment that need assessment. Heart development is an extremely sensitive process, which can be affected by environmentally toxic molecule exposure during embryonic development. Congenital heart defects are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 89 publications
(129 reference statements)
1
72
0
Order By: Relevance
“…Given these encouraging data, we investigated additional toxicity parameters on zebra sh embryos by monitoring the effects of increasing concentrations of JVG045 and corresponding percentages of DMSO on heartbeat. The normal zebra sh embryonic heartbeat rate is 140-180 beats per minute (bpm); this parameter is an established criterion for the evaluation of substance toxicity (39). Our analyses showed that heartbeat rates did not differ from data reported in the literature across all concentrations (DMSO average 142.0 bpm ± 11.17 SD; JVG045 average 138.4 bpm ± 12.95).…”
Section: Resultsmentioning
confidence: 53%
“…Given these encouraging data, we investigated additional toxicity parameters on zebra sh embryos by monitoring the effects of increasing concentrations of JVG045 and corresponding percentages of DMSO on heartbeat. The normal zebra sh embryonic heartbeat rate is 140-180 beats per minute (bpm); this parameter is an established criterion for the evaluation of substance toxicity (39). Our analyses showed that heartbeat rates did not differ from data reported in the literature across all concentrations (DMSO average 142.0 bpm ± 11.17 SD; JVG045 average 138.4 bpm ± 12.95).…”
Section: Resultsmentioning
confidence: 53%
“…Cardiotoxicity was also evaluated in vivo using a wild-type zebrafish (AB) strain and a cmlc2 EGFP transgenic zebrafish The zebrafish provides an extremely useful in vivo model in which to study the effects of drugs or toxic substances on vertebrate development, and particularly on cardiac development [16,17]. A previous report found that the overall predictive success rate of zebrafish for cardiotoxicity was 100% [18].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unsuitable to model pseudokinases in a zebrafish model. (6) The drug exposure method for zebrafish is mainly bathing, and caution should be taken with insoluble drugs and drug metabolism . Therapeutic antibodies are large therapeutic molecules that differ from small molecule agents in absorption, distribution, and elimination properties between the two classes of drugs in a systematic manner .…”
Section: Research Gaps Challenges Perspectives and Opportunities Tmentioning
confidence: 99%
“…(6) The drug exposure method for zebrafish is mainly bathing, and caution should be taken with insoluble drugs and drug metabolism. 465,466 Therapeutic antibodies are large therapeutic molecules that differ from small molecule agents in absorption, distribution, and elimination properties between the two classes of drugs in a systematic manner. 467 (1) Absorption: the absorption of small and large molecules differs with respect to their common extravascular routes of delivery (oral for small molecule agents versus injection for antibodies).…”
Section: Zebrafish Modelmentioning
confidence: 99%